Handbook of membrane separations : chemical, pharmaceutical, food, and biotechnological applications - Pabby, Anil Kumar; Rizvi, S. S. H., 1948-; Sastre, Ana Maria (CRC Press, 2015)
MEMBRANE APPLICATIONS IN CHEMICAL AND PHARMACEUTICAL INDUSTRIES AND IN CONSERVATION OF NATURAL RESOURCES. Membranes applications in chemical and pharmaceutical industries and in conservation of natural resources: An Introduction. Advanced Materials in Ultrafiltration and Nanofiltration Membranes. Reverse Osmosis Membrane. Industrial application of membrane contactors. Membranes applications in oil refining and petrochemical industry. Membrane and monolithic convective chromatographic supports. Membranes in gas separation. Pervaporation: theory, practice and applications in the chemical and all.